Escherichia coli O88 induces intestinal damage and inflammatory response through the oxidative phosphorylation and ribosome pathway in Pekin ducks - Li, Chong; Li, Shuzhen; Liu, Jinmei; Cai, Huiyi; Liu, Guohua; Deng, Xuejuan; Chang, Wenhuan (Frontiers in Cellular and Infection Microbiology, 2022)
Colibacillosis is one of the major health threats in the poultry industry worldwide. Understanding the pathogenic mechanisms involved in E. coli-induced inflammatory response may lead to the development of new therapies to combat the disease. To address this, a total of 96 one day-old male lean Pekin ducklings were employed and randomly allocated to 2 treatments, each contains 6 replicates of 8 ducks. Ducks in experiment group (EG) and control group (CG) were separately orally administered with 0.2 mL pathogenic E. coli O88 (3 × 109 CFU/mL) or equivalent volumes of 0.9% sterile saline solution at day 7, two times with 8 h interval. Serum and intestinal samples were collected at days 9, 14 and 28. Result showed that, ducks challenged with E. coli had lower average daily gain and higher feed intake/weight gain during days 9-14 and overall (P < 0.05). Histopathological examination showed that E. coli decreased the villus height and the ratio of villus height/crypt depth in jejunum (P < 0.05) at days 9 and 14. Intestinal barrier was disrupted, presenting in E. coli ducks having higher serum DAO and D-LA at days 9 and 14 (P < 0.05), and greater content of serum LPS at day 9 (P < 0.05). E. coli infection also triggered a systemic inflammatory response including the decrease of serum IgA , IgM and jejunal sIgA at day 14 (P < 0.05). In addition to these, 1062 differentially expressed genes were detected in jejunum tissues of ducks by RNA-Seq, including 491 upregulated and 571 downregulated. Based on KEGG database, oxidative phosphorylation and ribosome were the most enriched. These findings reveal the candidate pathways and genes that may be involved in E. coli infection, allow a better understanding of the molecular mechanisms of inflammation progression and may facilitate the genetic improvement of duck, provide further insights into tackle the drug sensitivity and animal welfare issue.